Outcome of Detachable Balloon Embolization in Traumatic Carotid Cavernous Fistula - Rujimethapass, Sujin (Asian Journal of Neurosurgery, 2025)
Objectives This article evaluates the outcomes and efficacy of detachable balloon embolization by single balloon delivery catheter, while identifying factors associated with successful embolization in traumatic carotid cavernous fistula (TCCF) patients.Materials and Methods We retrospectively collected data of TCCF patients who underwent detachable balloon embolization during March 2020 to April 2024. All cases utilized a single balloon delivery catheter for detachable balloon deployment (GOLDBAL, BALT Extrusion, France). We analyzed demographic, clinical, imaging, and angiographic data, including outcomes, complications, and factors associated with successful embolization.Results Thirty patients were treated with detachable balloon embolization. The mean age of the patients was 41.1 years (range 17–65 years). The median duration of symptom was 2.0 months (range 0.25–60 months). The most common mechanism of injury is motorcycle accident (83.3%). Nearly all patients had eye redness and proptosis. Angiographic data indicated 29 patients (96.7%) had drainage to the inferior petrosal sinus, 28 (93.3%) had drainage to the superior ophthalmic vein, and 8 (26.7%) had drainage to the superior petrosal sinus. Five cases (16.7%) were classified as small-sized fistula, 19 (63.3%) as medium-sized, and 6 (20%) as large-sized. Regarding the location of the fistula, 8 cases (26.7%) were found in the horizontal segment, while 22 cases (73.3%) were located in the ascending or genu segment of the cavernous internal carotid artery (ICA). Among the 24 patients (80%) who underwent successful embolization, the ICA was preserved in 23 out of 24 patients (95.8%). The remaining patient had ICA occlusion but exhibited no clinical symptoms. Residual cavernous aneurysm was found in two patients, one patient had persistent cranial nerve deficit, while the other was asymptomatic. Statistical analysis demonstrated a significant difference was associated with the fistula location at the ascending or genu segment of the cavernous ICA in relation to successful embolizationConclusion Despite the availability of several endovascular treatment options for TCCF, using detachable balloon embolization is a relatively straightforward procedure. When combined with a thorough understanding of cavernous sinus anatomy, this approach can significantly enhance the occlusion rate and preserve ICA patency while minimizing complications, particularly when the fistula is located at the ascending or genu segment of the cavernous ICA.
Keywords: direct carotid cavernous fistula; traumatic neurovascular injury; detachable balloon; balloon embolization; traumatic carotid cavernous fistula